Mediastinal ganglionar tuberculosis postcardiac transplantation - João Bruno Ribeiro Machado Lisboa; Guilherme de Abreu Rodrigues; Diego Corsetti Mondadori; João Paulo Cassiano de Macedo; Orival De Freitas Filho; Paulo Manuel Pêgo-Fernades (International Journal of Mycobacteriology, 2018)
The diagnosis and treatment of tuberculosis (TB) in transplanted receivers presents several challenges. TB is an opportunistic infection with high morbidity and mortality in solid organs of transplanted patients, therefore, the diagnosis difficulties. A case of a 30-year-old male, heart transplanted patient, who after being submitted to mediastinoscopy, obtained a result of lymph node TB.